Hemoadsorption treatment with CytoSorb® in patients with extracorporeal life support therapy: A case series. Issue 6 (June 2020) - Träger, Karl; Skrabal, Christian; Fischer, Guenther; Schroeder, Janpeter; Marenski, Larissa; Liebold, Andreas; Reinelt, Helmut; Datzmann, Thomas
Introduction: Extracorporeal life support is an increasingly used technique for respiratory and cardiocirculatory support. Besides primary organ dysfunction, an excessive systemic hyperinflammatory response can be the underlying cause for acute organ failure necessitating extracorporeal life support therapy, or it may be associated with the extracorporeal life support itself. Controlling this overwhelming inflammatory response using CytoSorb ® hemoadsorption has been shown to be associated with improved hemodynamics and restored metabolic balance resulting in preserved organ functions. Methods: In this retrospective case series, we describe 23 patients undergoing extracorporeal life support therapy and CytoSorb hemoadsorption. Cytokine levels were monitored, hemodynamic and metabolic variables were recorded, and outcome measures such as duration of organ support, intensive care unit mortality, and hospital mortality were noted. Results: CytoSorb treatment was associated with a trend toward a reduction in plasma cytokine levels (first treatment median interleukin-6 pre 595 vs post 350 pg/mL (n.s.); second treatment median interleukin-6 317 vs 108 pg/mL, p < 0.05), a reduced vasoplegic response resulting in a reduction in vasopressor requirements (first treatment median norepinephrine pre 0.15 vs post 0.02 µg/kg/min (n.s.); second treatment median norepinephrine 0.1 vs 0.02 µg/kg/min, p < 0.05) as well as rebalancing of deranged metabolic parameters (first treatment median lactate pre-treatment 6 vs post-treatment median lactate 2 mmol/L, p < 0.05). The hemoperfusion treatment was well tolerated and safe, without the occurrence of any CytoSorb device-related adverse events. Conclusion: Hemoadsorption may offer a potentially promising therapeutic option for critically ill patients undergoing extracorporeal life support therapy, with cytokine reduction and a consecutively mitigated inflammatory response, decreased vasoplegia, and improved organ function as seen in our patients.